EXPECTATION GAP MAHASISWA, AUDITOR DAN MANAJER TERHADAP SIKAP DAN KINERJA AUDITOR - Etty M. Nasser; F. Agathasari Ayuningtyas. R (Media Riset Akuntansi, Auditing & Informasi, 2007)
The objective of this research is to discover whether there are different perceptions among students, auditors and managers about the attitude and perfomiance of the auditors that can cause a condition that is known as expectation gap. This expectation gap includes the important aspects of the auditing process and the auditor's responsibility, the causes that influence the auditor's performance, the auditor's integrity to his client and the auditor's attitude to his client The questionnaire used in this research to collect data is the modification model from the Humprey, Moizer and S. Turley (1993) research questionnaire. Data are gathered through directly questionnaire, which collected from 120 respondents. There are 40 respondents from experienced auditor group from KAP, 40 respondents from finance managers as the audited result financial report user and 40 respondents from Trisakti students who majoring accountancy that have joined auditing class completely The tech-nique of convenience sampling is applied in gathering the data while the data are analyzed by using oneway ANOVA and Kruskal Waffis. The ANOVA test is used for analysis the normally distributed data and kruskal waffis test is used for analysis the abnormal distributed data. The result of this research shows that there are some differences in perceptions among the students, auditors and managers about the integrity and performance of the auditors for the first hypothesis. However, for the second, third and fourth hypothesis show no perception difference among the students, auditors and managers about the attitude and performance of the auditors.Keywords : Audito's performance, expectation gap, auditor's integrity